Desenvolvimento, caracterização e aplicação de sistemas de liberacão controlada de NPK à base de polímeros de glicerol usados no cultivo da alface - Pimenta, Igor Fernandes (2020)
The manufacture of controlled release systems using glycerol polymers as encapsulating matrices appears as an alternative to the use of excess glycerol, the main by-product of biodiesel. This also helps to minimize losses caused by leaching and volatilization of nutrients, reducing agricultural production costs. This work reports the study, characterization and application of glycerol polymers for uses in controlled release systems as NPK (Nitrogen, Phosphorus, Potassium) encapsulating matrices for soil tests in the cultivation of Regina lettuce (Lactuca sativa L.). Poly (glycerol adipate)-PGA, poly (glycerol citrate)-PGC, poly (glycerol succinate)-PGSu and poly (glycerol adipate-cosuccinate)-PGASu were produced by polycondensation of glycerol and diacids, followed by the incorporation of the NPK fertilizer in a content of 20% in relation to the mass of the polymers. The polymers/copolymers were characterized by thermogravimetry (TG), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), dispersed energy spectroscopy (EDS), contact angle, soil biodegradation, chemical analysis: H + Al + 3, Ca + 2, + Mg + 2, (S-SO4-2), P, K, SB (sum of bases), Carbon and Organic Matter, through atomic and flame absorption spectrophotometry, by titration and physical analysis (Temperature and humidity) of (soil and air) using a digital thermometer, and agronomic characteristics of lettuce plant height (AP), number of leaves (NF), fresh weight (MFPA) and dry mass of the aerial part (MSPA), fresh root weight (MFR), dry root weight (MSR) and average stem diameter (DC). FTIR analyzes showed that all polymers / copolymers are polyesters, evidenced by the formation of ester groups, and TG proved thermal stability of up to 200 ° C. Two types of fracture surfaces were observed, characteristic of rubbery (rough) and rigid (smooth and brittle) polymers, related to the structures of the polymers/copolymers. The incorporation of NPK favored the development of hydrophilic surfaces. Biodegradation in simulated soil was observed through a change in color and loss of mass during 120 days. The mass loss was 80% and does not depend on the type of polymer and NPK content. The EDS tests collaborated to verify the elemental components of the fertilizers in the polymers and in the leaves of the lettuce. The concentration of fertilizer (NPK) in the lettuce leaves and the agronomic characteristics revealed an excellent performance of each polymer/copolymer and that the results of nutrient release were superior compared to the results found in the references (white). Among the polymers, PGC + 20% NPK, obtained a superior performance compared to the others with the fertilizer (PGA, PGSu and PGASu), in agronomic characteristics. In addition, it was possible to demonstrate that controlled release systems using the glycerol polymer as encapsulators for NPK fertilizers, are feasible for use in agriculture in order to add final value to glycerol and that they can be modulated for a given type of crop.